Living Sufism of Sheikh Ahmad Mutamakkin in Tradition and Culture of Kajen Muslim Community - Alnashr, M Sofyan; Nisfa, Nia Lailin; Linnas, Mohammad Ghoffarul (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
Sheikh Ahmad Mutamakkin was a prominent Islamic scholar who played a significant role in spreading Sufism in the northern coastal region of Central Java, particularly in Pati. This study aims to explore how the concept of